"If in doubt, sit them out": How long to return to elite cycling competition following a sports-related concussion (SRC)? - Heron, N.; Jones, N.; Cardwell, C.; Gomes, C. (International Journal of Environmental Research and Public Health, 2024)
Introduction: A concussion or sports-related concussion (SRC) is a traumatic brain injury induced by biomechanical forces. After a SRC diagnosis is made, a concussed individual must undergo a period away from competition while they return to their baseline level of functioning. The Union Cycliste Internationale (UCI) currently recommend a minimum of 6 days restriction from competitive cycling following a SRC but there is a growing feeling amongst those involved in brain injury research that this period is too short. Therefore, how much time should cyclists be removed from competitive sporting action following a SRC? Aims: To review the time out of competition following the diagnosis of a SRC for elite cyclists within British Cycling (BC).